2017
DOI: 10.1002/jcla.22246
|View full text |Cite
|
Sign up to set email alerts
|

Decreased frequency of circulating Th9 cells in patients with chronic hepatitis B infection

Abstract: The depletion of Th9 cells is associated with the development of chronic HBV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Th9 and Tc9-secreting IL-9 still strongly inhibited coxsackie virus B3 replication without induction of apoptosis in cardiomyocytes ( 24 ), although the viral myocarditis did not mainly contribute to differentiation and proliferation of Th9 cells ( 25 ). In line with previous report ( 9 ), our current results suggested a decreased serum IL-9 and circulating non-specific and HBV-specific Th9 cells, but not Tc9 cells, in CHB and hepatitis B-related HCC. This indicated that decreased Th9 cells might mainly account for down-regulation of IL-9 during chronic HBV infection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Th9 and Tc9-secreting IL-9 still strongly inhibited coxsackie virus B3 replication without induction of apoptosis in cardiomyocytes ( 24 ), although the viral myocarditis did not mainly contribute to differentiation and proliferation of Th9 cells ( 25 ). In line with previous report ( 9 ), our current results suggested a decreased serum IL-9 and circulating non-specific and HBV-specific Th9 cells, but not Tc9 cells, in CHB and hepatitis B-related HCC. This indicated that decreased Th9 cells might mainly account for down-regulation of IL-9 during chronic HBV infection.…”
Section: Discussionsupporting
confidence: 93%
“…IL-9-producing T cells and IL-9 secretion contributes to tumor immunity and immune-related diseases, which provides useful insight into pathogenesis and treatment ( 7 , 8 ). Cui et al revealed that circulating Th9 cells was notably lower in chronic hepatitis B (CHB) patients, and no significant differences in Tc9 percentage between CHB patients and controls ( 9 ). However, the profile of viral specific Th9 and Tc9 cells and regulation of IL-9 secretion in HBV-related HCC was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, another group of investigators reported there was no significant difference in the percentage of Th9 cells, serum IL9 and IL10 levels among different groups (CHB and CHB-LC), no change in the percentage of Th9 cells before and after antiviral treatment in CHB patients, and no obvious correlation between the percentage of Th9 cells, levels of IL9, and IL10 with age, total bilirubin, albumin, ALT, and HBV DNA levels [ 44 ]. Similarly, Cui, et al [ 45 ] showed that the frequency of circulating Th9 cells was significantly lower in chronic HBV patients than controls, and the percentages of Th9 cells were negatively correlated with HBV DNA loads. The discrepancies might be explained, at least in part, to the difference in levels of HBV DNA load and the difference in study populations.…”
Section: Discussionmentioning
confidence: 93%
“…In China, the majority of patients with HCC are also believed to be chronically infected with HBV, a conclusion that was drawn based on virus-free mouse models, which admittedly differ from HCC patients with HBV. The effects of whole-cell vaccine and HBV cross-interaction on Th9 cells should be further studied to identify possible dual effects of Th9 cells in HCC (40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%